Angiotensin‐converting enzyme 2 antagonizes angiotensin II‐induced pressor response and NADPH oxidase activation in Wistar–Kyoto rats and spontaneously hypertensive rats. Issue 1 (27th July 2012) - Lo, Jennifer; Patel, Vaibhav B.; Wang, Zuocheng; Levasseur, Jody; Kaufman, Susan; Penninger, Josef M.; Oudit, Gavin Y.
<x xml:space="preserve">Abstract</x> Angiotensin‐converting enzyme 2 (ACE2), a monocarboxypeptidase capable of metabolizing angiotensin II (Ang II) into angiotensin‐(1–7) [Ang‐(1–7)], has emerged as a potential therapeutic target. We hypothesized that ACE2 is a negative regulator of Ang II‐mediated pathological effects in vivo. In Wistar–Kyoto (WKY) rats, Ang II infusion (0.1 μg min−1 kg−1) induced a pressor response, activation of NADPH oxidase and generation of superoxide in the heart, kidney and blood vessels; these effects were significantly blunted by recombinant human ACE2 (rhACE2; 2 mg kg−1), in association with a lowering of plasma Ang II and elevation of Ang‐(1–7) levels. In the spontaneously hypertensive rat (SHR) model, rhACE2 (2 mg kg−1 day−1) delivered over a 14 day period partly corrected the hypertension, the NADPH oxidase activation and the increased superoxide generation in the heart, kidney and blood vessels. Treatment with rhACE2 inhibited Ang II‐mediated phosphorylation of the myocardial extracellular signal‐regulated kinase 1/2 pathway in WKY rats, with congruent results seen in SHR hearts. Hence, rhACE2 is an important negative regulator of the Ang II‐induced pressor response and NADPH oxidase activation and suppresses pathological myocardial signalling, thereby providing a novel therapeutic agent with which to antagonize an activated renin–angiotesin system.